PSYCHOLOGISM OF CHILD CHARACTER IN THE WORKS OF SUSAN HILL - Tokhirova, Dilrabo (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
The article analyzes the complex relationship between the young boy James Burnett and his friend Mart May in Susan Hill’s “The Boy Who Taught the Beekeeper to Read” from the perspective of literary psychologism. Literary psychologism is an approach that focuses on a deep exploration of the inner emotions and psychological states of characters within a work. The study is aimed to illuminate James’s internal conflicts and fears through his naivety, curiosity, and vulnerability. The discussion centers on three primary methods: the author’s descriptions, dialogues, and nature imagery, all of which play a crucial role in reflecting the psychological state of the child. The author’s descriptions evoke empathy in the reader by portraying James’s physical and emotional conditions. Dialogues provide significant insights into James’s anxieties and aspirations, particularly revealing the intricacies of his relationship with Mart Mey. Furthermore, nature imagery creates a contextual backdrop that reflects James’s mental state, hinting at his internal struggles while emphasizing the fragility of his situation. This study uncovers essential themes such as childhood responsibility, loneliness, growth, and self-awareness within the story. The article employs a hermeneutic analysis to offer a clearer understanding of James’s psychological state, allowing readers to grasp his emotional experiences more profoundly. The findings contribute to the advancement of new theories and approaches within the realm of literary psychologism, enriching the field of childhood psychology research.